2016
DOI: 10.1007/s00253-016-7469-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microbial community structures due to varying operational conditions in the anaerobic digestion of oxytetracycline-medicated cow manure

Abstract: Management of manure containing veterinary antibiotics is a major concern in anaerobic treatment systems because of their possible adverse effects on microbial communities. Therefore, the aim of study was to investigate how oxytetracycline (OTC) influences bacteria and acetoclastic and hydrogenotrophic methanogens under varying operational conditions in OTC-medicated and non-medicated anaerobic cow manure digesters. Concentrations of OTC and its metabolites throughout the anaerobic digestion were determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…But among the four types of anaerobic microorganisms, methanogens are the least tolerant to environmental toxicants due to their slow growth rate and are most likely to be inhibited by antibiotics . Turker et al observed temporary changes in the bacterial community structure and a decrease in the diversity during AD of oxytetracycline‐medicated cow manure. However, certain bacterial groups recovered after a short period of adaptation, suggesting that they were tolerant of oxytetracycline and the metabolites.…”
Section: Mechanisms Of Antibiotic Inhibitionmentioning
confidence: 99%
See 4 more Smart Citations
“…But among the four types of anaerobic microorganisms, methanogens are the least tolerant to environmental toxicants due to their slow growth rate and are most likely to be inhibited by antibiotics . Turker et al observed temporary changes in the bacterial community structure and a decrease in the diversity during AD of oxytetracycline‐medicated cow manure. However, certain bacterial groups recovered after a short period of adaptation, suggesting that they were tolerant of oxytetracycline and the metabolites.…”
Section: Mechanisms Of Antibiotic Inhibitionmentioning
confidence: 99%
“…However, certain bacterial groups recovered after a short period of adaptation, suggesting that they were tolerant of oxytetracycline and the metabolites. Compared with the bacterial community, the effect of antibiotics on methanogenic archaea is more pronounced . According to Bauer et al, the presence of chlortetracycline (8000 mg kg −1 dry matters) did not significantly affect the 16S rRNA gene copy number of fermentative bacteria, while it dramatically reduced the 16S rRNA gene copy number of methanogens by >50%.…”
Section: Mechanisms Of Antibiotic Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations